Fiscal Rules and Public Spending: Evidence from Italian Municipalities - Wildmer Daniel Gregori (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
The aim of this paper is to investigate the extent to which local budget spending composition reacts to fiscal rules variations. I consider the budget of Italian municipalities and exploit specific changes in the Domestic Stability Pact's rules, to perform a difference-in-discontinuities analysis. The results show that not all rules are equally effective: imposing a cap on the total amount of consumption and investment is not as binding as two caps, one specific for consumption and a different one for investment spending. More specifically, the consumption variation is triggered by changes in the level of wages and services spending, while investment relies on infrastructure movements. In addition, there is evidence that when an increase in investment is achieved, there is also a higher budget deficit level.
Keywords: C21; C23; H72; H74; H77; 330